2021
DOI: 10.3390/diagnostics11081403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Loading Changes on the Intraventricular Pressure Measured by Color M-Mode Echocardiography in Rats

Abstract: Evaluation of diastolic function is a pivotal challenge due to limitations of the conventional echocardiography, especially when the heart rate is rapid as in rats. Currently, by using color M-mode echocardiography (CMME), intraventricular pressure difference (IVPD) and intraventricular pressure gradient (IVPG) in early diastole can be generated and are available as echocardiographic indices. These indices are expected to be useful for the early diagnosis of heart failure (HF), especially diastolic dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…In the present report, the postoperative E wave was higher than the preoperative measurement, likely caused by the decreased mitral orifice area following the device placement. The E wave is sometimes used for the estimation of atrial pressure; however, the E wave can be affected by multiple factors, including preload, diastolic function, and others [ 18 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present report, the postoperative E wave was higher than the preoperative measurement, likely caused by the decreased mitral orifice area following the device placement. The E wave is sometimes used for the estimation of atrial pressure; however, the E wave can be affected by multiple factors, including preload, diastolic function, and others [ 18 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent echocardiographic approaches such as two-dimensional speckle tracking echocardiography (2D-STE) and intraventricular pressure gradients (IVPG) calculated from color M-mode echocardiography create a breakthrough in cardiology research for the early diagnosis of cardiac dysfunctions, as compared with other traditional methods [ 16 , 17 , 18 ]. In the present report, the echocardiographic changes were evaluated using conventional echocardiography, 2D-STE and CMME, before and weekly after the implantation of the TEER in two clinically normal dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Current cardiovascular research focuses on the development of non-invasive diagnostics for diastolic dysfunction. This is because heart failure with preserved ejection fraction (HFpEF) is known to account for half of the patients diagnosed with end-stage heart failure, and the accurate diagnostic methods are challenging and have not yet been established ( 17 ). Evaluation of diastolic function using conventional echocardiography is limited as the measurements are affected by the heart rate and arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the fact that E wave velocity, E′, and E/E′ also showed no differences between the groups, it is easily concluded that LA pressure was not elevated in the UC group. The usefulness of 2DSTE and IVPG for assessing cardiac function was confirmed in rats before ( 12 , 13 , 34 ). Myocardium dysfunction detected by STE combined with the fact that intracardiac flow was not disturbed in UC to provide us with an interesting conclusion: subtotal nephrectomy induced UC rat model could be used for cardiovascular drug selection.…”
Section: Discussionmentioning
confidence: 82%
“…Intraventricular pressure gradients (IVPG), the pressure gradients inside the ventricle that draw blood from the left atrium (LA) to the LV during diastole, have been strongly correlated with left atrial (LA) pressure and active relaxation ( 10 ). Our previous research proved that IVPG could be used as a serial cardiac function evaluation tool in rodent and dog models ( 11 13 ).…”
Section: Introductionmentioning
confidence: 98%